2012
DOI: 10.1007/s13580-012-0072-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ethanol released from aged radish (Raphanus sativus L.) seeds using resazurin

Abstract: The release of volatiles from aged radish (Raphanus sativus L., var. Yechanmoo) seeds and from ethanol was evaluated using the resazurin reagent (RR, solution of resazurin and yeast mixture). The primary volatile released from the aged radish seeds was identified as ethanol, but no volatiles from non-aged seeds were detected by solid phase microextraction (SPME) followed by GC-MS analysis and ethanol standard confirmation. The volatiles from aged radish seeds and from ethanol changed the color of the RR from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Methanol and ethanol production was also observed in C. carvi seeds ( Fig. 3 ) and has previously been reported in other species ( Bicanic et al , 2003 ; Buckley and Buckley, 2009 ; Colville et al , 2012 ; Kodde et al , 2012 ; Lee et al , 2000 ; Min, 2012 ; Mira et al , 2010 ; Rutzke et al , 2008 ; Taylor et al , 1999 ; Zhang et al , 1993 , 1994 , 1995b ; Zhang and Roos, 1997 ). In contrast, seeds of E. vesicaria produced acetaldehyde and acetone under humid conditions ( Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Methanol and ethanol production was also observed in C. carvi seeds ( Fig. 3 ) and has previously been reported in other species ( Bicanic et al , 2003 ; Buckley and Buckley, 2009 ; Colville et al , 2012 ; Kodde et al , 2012 ; Lee et al , 2000 ; Min, 2012 ; Mira et al , 2010 ; Rutzke et al , 2008 ; Taylor et al , 1999 ; Zhang et al , 1993 , 1994 , 1995b ; Zhang and Roos, 1997 ). In contrast, seeds of E. vesicaria produced acetaldehyde and acetone under humid conditions ( Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The assay is an accurate and convenient seed vigour test compared to gas chromatography and tests based on germination and the TZ test, as well as detecting ethanol released from seeds using Resazurin (Brand and Nicholls, 2011;ISTA, 2015;Min, 2012). The fast ethanol assay requires 2-3 h for complete analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Tamogami et al investigated the biosynthetic pathway of methyl (E)-2-hexenoate in Achyranthes bidentata plant and suggested that Achyranthes bidentata possess a specific pathway for the production of methyl (E)-2-hexenoate (1) from (Z)-2-hexenol in response to methyl jasmonate [108]. In another work, Min used SPME-GC-MS method and resazurin reagent to study ethanol released from aged radish seeds [109].…”
Section: Stems Roots and Seedsmentioning
confidence: 99%